Cutting-edge extraction technologies for anticancer compounds from ethnomedicinal mulberry: A molecular review in cancer management - Akhileshwar Kumar SRIVASTAVA; Sunil L.; Gayathri THULASY; Subrahmaniam Gandhi DOSS; Divya SINGH (Notulae Scientia Biologicae, 2025)
Cancer is one of the most challenges diseases in modern medicine, imposing innovative methods for prevention and treatment. Currently, mulberry belonging to Moraceae family has gained special attention because of its phytochemical constituents (flavonoids, polysaccharides, alkaloids, polyphenols, and anthocyanins) and its positive impacts on human healthiness like antioxidant, antidiabetic, and immunomodulatory action. Historically, different parts (fruits, leaves, twigs, roots) of Morus sp. have been employed as traditional regimens for treatment of several infectious and internal ailments. Several reports have described about anticancer properties of mulberry. It has been explored their multifaceted mechanisms of action such as anti-proliferative, pro-apoptotic, cell-cycle arrest, mitotic catastrophe, anti-metastasis in different cancers. However, the international scientific societies have not made much attention to explore the anticancer properties of mulberry’s components for cancer treatment. Currently, cutting-edge technologies are playing crucial role to identify the specific anticancer compounds of mulberry. This review acquires current knowledge on mulberry phytochemicals and their intricate molecular interactions within cancer cells as well as their synergistic impacts with conventional drugs to enhance therapeutic potential in cancer treatment. Also, it delves about some major cutting-edge technologies to extract the specific anticancer compounds from mulberry.